PEMANFAATAN ANIMASI MACROMEDIA FLASH DALAM MENINGKATKAN HASIL BELAJAR - Asyti Febliza; Zul Afdal (UIR Press, 2019)
Abstract This study aims to implement macromedia flash animation in improving student learning outcomes on the topic of buffer solutions. This research was conducted in the first semester of the basic chemistry course with the topic of buffer solution. The samples in this study were first semester students at the University of Riau divided in 2 classes. This study is quasi-experimental, by making treatment in the experimental class (animation class) by comparing with the control group. The hypotheses tested in this study are: Ha = There are differences in the level of learning outcomes of the experimental class and the control class and H0 = There is no difference in the level of learning outcomes of the experimental class and the control class. Hypothesis testing is done by the independent sample T-Test on SPSS 22 with a significance level of 0.05 which used gain score. Based on the results and discussion it can be concluded that the experimental class has an increase in learning outcomes by 57%, while the increase in student learning outcomes in the control class is only 39%, which is about 2/3 of the increase in learning outcomes of the experimental class. Based on the results of the hypothesis test it can be concluded that Ha is accepted, namely there are differences in the level of learning outcomes of experimental class and control class where significance is equal to sig = 0.000, this value is smaller than the significance level of 0.05. Keywords: animation, macromedia flash, learning media, learning outcomes, buffer solutions